A 3‐year longitudinal prospective study assessing microbial profile and clinical outcomes of single‐unit cement‐retained implant restorations: Zirconia versus titanium abutments. (5th February 2020) - de Oliveira Silva, Thalisson S.; de Freitas, Alice R.; de Albuquerque, Rubens F.; Pedrazzi, Vinícius; Ribeiro, Ricardo F.; do Nascimento, Cássio
Abstract: Purpose: The aim of this study was to assess the microbiological and clinical outcomes of implant‐supported restorations on zirconia or titanium abutments after 3 years in function. Materials and methods: Twenty two‐part dental implants were placed in 20 healthy individuals in need of single‐tooth replacement. Ceramic‐based reconstructions were cemented in either zirconia or titanium abutments. Clinical, radiographic, and microbiological outcomes were examined at implant loading and then yearly up to 3 years post‐loading. Results: Cumulative survival/success implant rates were 95% after 3 years. Mean total marginal bone loss was 0.76 ± 0.21 mm for zirconia and 0.99 ± 0.41 mm for titanium, with no significant differences ( P > .05). Overall, titanium and zirconia abutments presented similar values of probing depth, gingival recession, and bleeding on probing over time ( P < .05). Microbial profile of implants restored with titanium or zirconia is quite similar to that found in the remaining teeth. Conclusions: Zirconia and titanium presented different microbial profile and genome counts. Clinical findings for both zirconia and titanium abutments were similar and consistent with a healthy condition, reflecting a high survival rate and low bone loss. Microbiota did not impact the clinical outcomes after 3 years of function.